PENGARUH KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI DI KANTOR BADAN ARSIP DAERAH PROVINSI KALIMANTAN TIMUR - Rakhmani, Aswin (PREDIKSI, 2014)
Influence Leadership Against Employee Job Satisfaction in the Office of the Provincial Archives of East Kalimantan.Â This study aims to determine whether the leadership has a positive influence on employee job satisfaction in the Office of the Provincial Archives of East Kalimantan.Â Â The results showed that there is a positive and significant relationship between the variables of leadership with employee job satisfaction variables in the Office of the Provincial Archives of East Kalimantan. It can be seen from the results of statistical tests where the correlation coefficient (r) is equal to 0.630, which means there is a strong and positive relationship between the two variables Leadership with job satisfaction.